Síntese e Caracterização de Novos Compostos Derivados de Bis(4-Aminobenzenoselenolato) de Mercúrio(II) e Bis(4-N,N-Dimetil-aminobenzenoselenolato) de Mercúrio(II) - Bublitz, Fabrício (2014)
This work presents the synthesis and structural analysis of the first compounds obtained through the use of the building blocks Mercury(II) bis(4-Aminobenzeneselenolate) Hg(SeC6H4NH2-4)2 and Mercury(II) bis(4-N,N-Dimethyl-Aminobenzeneselenolate) Hg(SeC6H4NMe2-4)2. Firstly, a synthetic procedure was adapted for the diaryl disselenides (4-H2NC6H4Se)2 (1a) e (4-Me2NC6H4Se)2 (1b), whose crystalline structures are been described here for the first time. From these disselenides, it were possible to obtain the mercury(II) selenolates Hg(SeC6H4NH2-4)2 (2a) e Hg(SeC6H4NMe2-4)2 (2b). By reacting 2a with mercury(II) halides and tricyclohexylphosphine, the complexes HgX(SeC6H4NH2-4)(PCy3) (3a, X = I and 3b, X = Br) and the pseudo dimer [HgCl(SeC6H4NH2-4)(PCy3)]2.2THF (4) were obtained. Instead, by reacting 2b with mercury(II) halides, the coordination polymer {[Hg2Br2(SeC6H4NMe2-4)2].DMF}n (5) and the polymeric cluster [Hg4Cl3(SeC6H4NMe2-4)5]n (6) were obtained. All the compounds with the exception of 2b were structurally determined by single crystal X-ray diffraction and 1(a-b), 2(a-b) were characterized by nuclear magnetic resonance. All the compounds were also analyzed by infrared vibrational spectroscopy and elemental analysis.